#TITLE_ALTERNATIVE# - AULIANOVA (NIM : 13605014); Pembimbing : Dr. Rais Zain, M.Eng ; Ir. M. Hindra Salim, ADINDA
Surface reconstruction from digitized data in the form of point clouds is one of the reverse engineering process sequences which is performed in order to improve production lines and or to improve manufacturing capabilities of a product. In this research, point clouds data was analyzed and transformed to become a reference surface of the front door of car. The reconstruction of reference surface in this research has been conducted for two different point clouds data formats; ASCII and CGO format. The reconstruction was performed by utilizing CATIA V5 (Computer Aided Three Dimensional Interactive Application Version 5). Essentially, the reconstruction process in CATIA consists of four stages. The first stage is the point clouds processing, followed by mesh creation stage, continued with section creation stage, and finalized with surface creation stage. The result of the reconstruction in this research can be used as a guideline for further detailed reconstruction. Evaluation of generated reference surface has been conducted in CATIA V5 using isophotes mapping analysis and distance analysis. The evaluation shows that isophotes analysis is able detect the continuity quality of interconnecting domain through a black and white contour visualization which shows connection smoothness between generated reference surfaces. The evaluation also shows that the distance analysis is suitable for analyzing, locating, and indicating local deviation amplitudes of reference surfaces compared with data point clouds.